2020
DOI: 10.3390/nano11010041
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress of Black Silicon: From Fabrications to Applications

Abstract: Since black silicon was discovered by coincidence, the special material was explored for many amazing material characteristics in optical, surface topography, and so on. Because of the material property, black silicon is applied in many spheres of a photodetector, photovoltaic cell, photo-electrocatalysis, antibacterial surfaces, and sensors. With the development of fabrication technology, black silicon has expanded in more and more applications and has become a research hotspot. Herein, this review systematic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 116 publications
0
33
1
Order By: Relevance
“…Black silicon (bSi) features surface textures from micro-to nanoscales, exhibiting reduced optical reflection and thus enhanced absorption. [1][2][3][4] It is generally acknowledged that the antireflection effect due to the surface textures contributes to the high absorptance for wavelengths below 1.1 μm, [5] which applies especially to the visible range (400-750 nm) and as a result the bSi shows darkened color to naked eyes. High visible absorption can be obtained with different fabrication methods with optimized surface morphology, and those methods include, e.g., electrochemical etching, [6] stain etching, [7] metal-assisted chemical etching, [8] reactive ion etching, [9] and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Black silicon (bSi) features surface textures from micro-to nanoscales, exhibiting reduced optical reflection and thus enhanced absorption. [1][2][3][4] It is generally acknowledged that the antireflection effect due to the surface textures contributes to the high absorptance for wavelengths below 1.1 μm, [5] which applies especially to the visible range (400-750 nm) and as a result the bSi shows darkened color to naked eyes. High visible absorption can be obtained with different fabrication methods with optimized surface morphology, and those methods include, e.g., electrochemical etching, [6] stain etching, [7] metal-assisted chemical etching, [8] reactive ion etching, [9] and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies that reported BSi production by ICP RIE methods either used expensive materials such as Pt 66 or textured the surface to produce pillars of higher reflectance than reported herein. 27 The coating of the textured silicon substrates with Al 2 O 3 , 67 NbN, 68 or other materials coupled with the use of highly energy demanding atomic layer deposition 69 or other methods improved the reflectance to 3%. 27 However, our work shows that BSi can be produced with reflectance lower than 3% in the visible region without the use of costly materials, coatings, or machinery.…”
Section: Resultsmentioning
confidence: 99%
“… 26 Conventional BSi production methods report the use of laser irradiation, metal-assisted chemical etching, wet etching such as HF etching, and RIE used herein among other methods. 27 RIE processes typically require the use of photoresists or some form of masking material. Therefore, in this work, we demonstrate how a bioavailable and nontoxic lignin material can be used to form the template for pattern transfer without the use of extensive machinery or high costs.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the surface nanostructures, nearly 80% of incident light is trapped and subjected to multiple reflections and transmissions, boosting the photons' absorption ability [9,10]. The exceptional properties of structured silicon provide a powerful support for devices such as photodetectors or solar cells, especially if wide response range and high responsivity performance is targeted [11][12][13]. Currently, the research has focused on improving the spectral response range and selectivity in silicon-based devices by developing many types of heterojunctions that integrate materials from organic to narrow band-gap semiconductors, metallic thin films and nanostructures.…”
Section: Introductionmentioning
confidence: 99%